2015
DOI: 10.1007/s12665-015-4395-6
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical background of potentially toxic trace elements in soils of the historic copper mining area: a case study from Miedzianka Mt., Holy Cross Mountains, south-central Poland

Abstract: The aim of this study was to evaluate the geochemical background and spatial distribution patterns of selected trace elements (As, Cd, Cr, Cu, Mn, Ni, Pb, U and Zn) in 62 surface soil samples collected in the historic Cu mining area (Miedzianka Mt., Holy Cross Mountains, south-central Poland). In the study area the mining activity dates back to the fourteenth century. After the shutdown of mining operations in 1953, the soil was not remediated and neither its mineralogy nor chemistry was examined. The examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…This was the case for coastal TP levels that exceed almost 100% with respect to the limits of Hawaii while background calculations suggested that levels were subject to natural increases that surpasses Hawaiian specific criteria for estuaries (3 NTU). Thus, the application of large-scale background values to evaluate local status of water quality is not recommended since local background is constrained by local conditions [17,18,21,22].…”
Section: Environmental Background Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was the case for coastal TP levels that exceed almost 100% with respect to the limits of Hawaii while background calculations suggested that levels were subject to natural increases that surpasses Hawaiian specific criteria for estuaries (3 NTU). Thus, the application of large-scale background values to evaluate local status of water quality is not recommended since local background is constrained by local conditions [17,18,21,22].…”
Section: Environmental Background Levelsmentioning
confidence: 99%
“…Alterations of water can pose a threat to public health and affect human access to safe water for drinking and domestic purposes, food production, and recreation [1]. In aquatic ecosystems, poor water quality can lead to detrimental effects such as the increase in algal biological processes, residence time of water, recharge inputs and transport processes [18,21]. For that reason, statistical methods are preferred for the calculation of local background levels.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, limited data exist on geochemical background of trace metal(loid)s in historic mining areas (Loredo et al 2006;Martínez et al 2007;Gałuszka et al 2015;Gutiérrez et al 2016). The quality of soils in these areas is very difficult to assess due to overlapping of anthropogenic and natural high concentrations of metal(loid)s and usually a very high variation of metal(loid) distribution patterns in soils .…”
Section: Introductionmentioning
confidence: 99%
“…Rejection of outlying values is not recommended because in environmental studies, they may carry a crucial information about the study area and potential “hot spots” (Gałuszka et al 2015). In this study, computed coefficients of skewness and shapes of histograms confirmed asymmetrical distribution of the majority of analyzed elements (Table 2).…”
Section: Resultsmentioning
confidence: 99%